Extrusion of the Distal Catheter From the Umbilicus: A Case Report of a Rare Complication After Ventriculoperitoneal Shunt and Its Management - Xia, Yi; He, Fang; Ren, Zhen; Wang, Chao (Frontiers in Pediatrics, 2020)
Spontaneous extrusion of the distal catheter from the umbilicus followed by a ventriculoperitoneal shunt (VPS) for the treatment of hydrocephalus is an extremely rare complication. Here, we describe an 8-year-old boy with a history of secondary communicating hydrocephalus who had a VPS placed which was extruded through the umbilicus. Fortunately, he was treated successfully after cutting off the extrusive part of the peritoneal catheter using a laparoscope. To the best of our knowledge, there are no reports of using laparoscopy to cut and replace the protruding part and replace the shunt end. By keeping the function of the original shunt pipe, this case report offers an innovative and informative approach for treating this complication.